2019
DOI: 10.1128/msphere.00676-19
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Global Network of Extracellular Protease Regulation in Staphylococcus aureus

Abstract: The complex regulatory role of the proteases necessitates very tight coordination and control of their expression. While this process has been well studied, a major oversight has been the consideration of proteases as a single entity rather than as 10 enzymes produced from four different promoters. As such, in this study, we comprehensively characterized the regulation of each protease promoter, discovering vast differences in the way each protease operon is controlled. Additionally, we broaden the picture of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 93 publications
2
52
2
Order By: Relevance
“…However, there is some contradictory evidence in this regard. For instance, several reports concluded that mutation of sarA has no impact on transcription of the spl operon [ 6 , 14 , 34 ] but we have demonstrated that all six Spl proteases are present in increased amounts in conditioned media (CM) from stationary phase cultures of a LAC sarA mutant by comparison to CM from LAC itself [ 27–29 ]. Irrespective of this discrepancy, it is clear that mutation of agr results in a decrease in overall protease activity to a degree that can be correlated with an increased capacity to form a biofilm, while mutation of sarA results in an increase in overall protease activity to a degree that can be correlated with a decreased capacity to form a biofilm [ 32 ].…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…However, there is some contradictory evidence in this regard. For instance, several reports concluded that mutation of sarA has no impact on transcription of the spl operon [ 6 , 14 , 34 ] but we have demonstrated that all six Spl proteases are present in increased amounts in conditioned media (CM) from stationary phase cultures of a LAC sarA mutant by comparison to CM from LAC itself [ 27–29 ]. Irrespective of this discrepancy, it is clear that mutation of agr results in a decrease in overall protease activity to a degree that can be correlated with an increased capacity to form a biofilm, while mutation of sarA results in an increase in overall protease activity to a degree that can be correlated with a decreased capacity to form a biofilm [ 32 ].…”
Section: Introductionmentioning
confidence: 80%
“…It has also become increasingly evident that the regulatory circuit modulating protease production extends far beyond these two loci. Indeed, mutations in argR2, arlRS, atlR, codY, hisR, mgrA, mntR, msaABCR, nsaR, rbf, rex, rot, rpiRB, saeRS, sigB, sarR, sarS, sarT, sarU, sarV, sarX, sarZ, xdrA, yjbh , and a number of uncharacterized putative regulatory loci have all been shown to impact the production of extracellular proteases [ 14 , 34 , 36–54 ]. A recent report directly compared the impact of mutating these loci on transcription of each of the four transcriptional units ( aur, scpAB, sspAB , and splA-F ) that encode aureolysin, ScpA, SspA, SspB, and SplA-F and concluded that the regulatory proteins encoded by seven of these loci (CodY, MgrA, Rot, SaeR, SarR, SarS, and SarA) constitute a primary network while those encoded by an additional seven loci (ArgR1, AtlR, MntR, Rbf, Rex, SarU, and XdrA) constitute a secondary network that functions primarily through its impact on regulatory elements within this primary network [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Streptococcus, competent stimulating factors can promote the regulation of the biofilm by the QS system [80]. In Staphylococcus epidermidis, QS system-related comprehensive regulator sarA is closely related to biofilm formation and is a positive regulator of Staphylococcus epidermidis biofilm formation [90,91] (Table 2).…”
Section: Regulation Of Bacterial Biofilm Formation By Qsmentioning
confidence: 99%
“…Inhibition of extracellular proteases has become a viable route to achieve synergy with small-molecule drugs and could also show synergy with MAPs. As a notable example, there is a key serine protease, SspA/V8, that is secreted by S. aureus [ 40 ]. This protein is crucial to microbial growth and adhesion that has been shown to degrade the MAP LL-37 [ 41 ].…”
Section: Synergy and Resistance To Mapsmentioning
confidence: 99%